METODE PENILAIAN KUALITAS DATA SEBAGAI REKOMENDASI SISTEM REPOSITORI ILMIAH NASIONAL - Riyanto, Slamet; Marlina, Ekawati; Subagyo, Hendro; Triasih, Hermin; Yaman, Aris (BACA: Jurnal Dokumentasi dan Informasi, 2020)
High quality data and data quality assessment which efficiently needed to data standardization in theresearch data repository. Three attributes most used i.e: completeness, accuracy, and timeliness aredimensions to data quality assessment. The purposes of the research are to increase knowledge anddiscuss in depth of research done. To support the research, we are using traditional review method on theScopus database to identify relevant research. The literature review is limited for the type of documentsi.e: articles, books, proceedings, and reviews. The result of document searching is filtered using somekeywords i.e: data quality, data quality assessment, data quality dimensions, quality assessment, dataaccuracy, dan data completeness. The document that found be analyzed based on relevant research. Then,these documents compare to find out different of concept and method which used in the data qualitymetric. The result of analysis could be used as a recommendation to implement in the data qualityassessment in the National Scientific Repository.